Identification of Combining Ability Patterns for Pearl Millet Hybrid Breeding in West Africa. Issue 4 (1st July 2019) - Sattler, Felix T.; Pucher, Anna; Kassari Ango, Issoufou; Sy, Ousmane; Ahmadou, Issaka; Hash, C. Tom; Haussmann, Bettina I. G.
ABSTRACT: Diets of West African (WA) smallholder farmers are built on pearl millet [ Pennisetum glaucum (L.) R. Br.]. Sustainable pearl millet hybrid breeding is challenging in WA, mostly due to an extensive genetic diversity combined with a high degree of admixture. In the absence of natural heterotic groups, understanding combining ability patterns can enable systematic development of heterotic groups and make sustainable hybrid breeding feasible. The objectives of this study were to evaluate heterosis and combining ability patterns and their relationship with genetic distance among WA pearl millets based on population hybrids, and to derive conclusions for future breeding programs. Therefore, 17 open‐pollinated varieties (OPVs) were crossed in a diallel mating design and tested together with their offspring in nine environments over 2 yr in Niger and Senegal. Genetic distances between the OPVs were evaluated with twenty microsatellite markers. Average panmictic better‐parent heterosis (PBPH) was 18% (1–47%) for panicle yield. A principal coordinate analysis based on genotyping results separated parental OPVs clearly by geographic origin. Although there was no relationship between genetic distance among OPVs and PBPH, we confirmed good combining ability among selected OPVs from Niger vs. Senegal. The identified cultivars (Nigerien CIVT, H80‐10Gr, and Taram and Senegalese Thialack 2 and Souna 3) with high combining ability are recommended for founding divergent heterotic pools targeting long‐panicle pearl millet hybrids. Our study shows the benefits of population hybrids and represents an important step to identify combining ability patterns and initial heterotic groups for WA pearl millet hybrid breeding.